2022
DOI: 10.3390/nursrep12030059
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Stress in Portuguese Oncology Nurses Delivering Palliative Care: A Pilot Study

Abstract: Oncology nurses often face complex end-of-life issues, underlining their need for specific training in palliative care. In this context, nurses experience several emotional and psychological dilemmas, which are often difficult to manage and result in high levels of workplace stress. This study aimed to determine the levels and work-related factors of workplace stress among oncology nurses. A descriptive baseline study was performed as part of a large four-phase study based on quantitative data collected from P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
4
9
0
Order By: Relevance
“…The nursing profession is generally associated with a high level of workload and work-related stress, especially for nurses who provide EoLC [5,7,8,[14][15][16]38]. The results obtained in this study indicated that the total mean value of the nurses' workload scale was 17.75 (range 7-35).…”
Section: Nurses' Workload When Providing Eolcmentioning
confidence: 61%
See 1 more Smart Citation
“…The nursing profession is generally associated with a high level of workload and work-related stress, especially for nurses who provide EoLC [5,7,8,[14][15][16]38]. The results obtained in this study indicated that the total mean value of the nurses' workload scale was 17.75 (range 7-35).…”
Section: Nurses' Workload When Providing Eolcmentioning
confidence: 61%
“…This indicates that almost all respondents understand and agree with involving patients in decision-making and respecting their wishes during EoLC. However, healthcare professionals in ICUs and other wards conducting EoLC are frequently under constant pressure applied by the patient's family to take all possible measures in order to keep a patient alive [5]. Preserving life at any cost has become a commonly accepted dogma in high-tech wards worldwide.…”
Section: Respondents' Agreement With Dysthanasiamentioning
confidence: 99%
“…The links between work life quality and care quality led National Health Authorities (such as the French Health Authority, HAS) to include work life quality (WLQ) as one of the dimensions to be considered in the certification of hospitals and to systematically integrate it into the quality assessment, as observed in other countries [ 1 , 2 , 3 , 4 , 5 ]. Based on the strong and close link between the well-being of patients and the well-being of caregivers, hospitals have implemented actions to improve the work life quality of their employees, which consequently contributes to improving the quality of patient care [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevention of occupational risks is part of WLQ, and it is a component that improves the physical work environment [ 2 , 10 ]. Among the occupational risks faced by care providers, musculoskeletal disorders are the leading cause of occupational illnesses and are responsible for significant absenteeism and high compensation costs.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses with less clinical experience may experience even more difficulties than their experienced counterparts in dealing with issues related to death and dying. 10 While some studies have examined the feelings and anxiety of nurses during the COVID-19 pandemic in emergency wards 11,12 and ICUs, [13][14][15] few studies have targeted acute care wards. 16 In addition to nurses directly involved in the care of COVID-19 patients being exhausted, those in acute care wards who were not directly involved experienced difficulties owing to staffing shortages and various restrictions.…”
mentioning
confidence: 99%